The Significance of Serum Ferritin and vitamin D Levels in Females Patients with Chronic Telogen Effluvium - Rana Talib Naser; Qayssar Joudah Fadheel; Ali Hatem Hafedh (Indian Journal of Forensic Medicine & Toxicology, 2021)
Back ground : Diffuse hair loss is a very common complaint usually occurs without inflammation or scarring.The loss affects hairs throughout the scalp in a more or less uniform pattern . That is characterized by theingress of a large number of hairs prematurely into telogen phase resulting in diffuse hair shedding at onetime often with an acute onset so named acute telogen effluvium .A chronic form with a more insidious onsetand a longer duration also exists called chronic telogen effluvium which primarily affects women betweenthe ages of 30 and 60 years and is a diagnosis of exclusion and can cause a great psychological impact onthe life of the affected person.Objective: Measurement the level of serum ferritin and the level of serum vitamin D In adult females withchronic telogen effluvium in order to validate their role in the process of hair loss .Patients& Methods : This cross-sectional study was conducted at the outpatient Department of Dermatologyand Venereology in Al-kindy Teaching Hospital between March and November 2017.Sixty adult Female atage (12 to 52 years) with hair loss in the form of CTE otherwise they are healthy and sixty adult healthy withsame age-matched female with no hair loss were included in the study. Diagnosis was based upon clinicalexamination as well as hair pull test. Serum ferritin and vitamin D levels and Hemoglobin were determinedfor each participant .Results : Hair loss can have an emotional impact on patients leading to anxiety and frustration. Therefore,diagnosing the underlying etiology is necessary for the better management of the disorder The results of thisstudy suggest that the reduced hair density seen in CTE may possibly be associated with low serum levelsof ferritin and vitamin D. It is recommended that hemoglobin level measurement should not be solely reliedon in the assessment of hair loss, as it was not significantly different between patients with CTE and controlsas seen in our study.Conclusions: The female cases in this study had significantly low levels of serum ferritin and vitamin D thancontrols .Our study highlights the importance of serum ferritin and vitamin D evaluation in case of diffusehair fall.